The Effect of Product Placement on Consumer Buying Interest with Brand Awareness as a Mediating Variable - Nanto Purnomo (International Journal of Integrative Sciences, 2023)
This study aims to determine whether there is a positive and significant influence between product placement on consumer buying interest. Does brand awareness have a positive and significant effect on consumer buying interest? Does brand awareness have a positive and significant effect on brand awareness? And can brand awareness bridge the influence of brand awareness on consumer buying interest in Cimory's healthy products? This type of research is quantitative research. The sampling technique uses a purposive technique. The data collection technique uses a questionnaire through Google Forms. Data analysis using SmartPLS 3.0 software. The results of this study indicate that Product Placement has a positive and significant effect on Consumer buying interest in Cimory products, Product Placement has a positive and significant effect on brand awareness of Cimory products, Brand awareness has a positive and significant effect on Consumer buying interest in Cimory products, Product Placement has a positive effect and significant impact on Consumer buying interest mediated by brand awareness